Early Childhood Development in Children Born to HIV-Infected Mothers: Perspectives From Kenyan Clinical Providers and Caregivers - Megan S. McHenry MS; Eren Oyungu MBChB, MMED; Carole I. McAteer MPH; Ananda R. Ombitsa BSc; Erika R. Cheng PhD, MPA; Samuel O. Ayaya MBChB, MMED; Rachel C. Vreeman MD, MS (SAGE Publishing, 2018)
Objective . To understand the perspectives of clinical providers and caregivers regarding early childhood development (ECD) in children born to HIV-infected mothers in Kenya. Methods . This was a qualitative study of provider and caregiver perspectives on ECD at 5 Kenyan HIV clinics, using semistructured interviews and focus group discussions. Constant comparison and triangulation methods were employed to elucidate the concepts of ECD. Results . Twenty-five providers and 67 caregivers participated. While providers understood ECD in terms of milestones, caregivers strongly equated ECD with physical growth. Factors affecting ECD, such as nutrition, perinatal effects, and illness, were perceived differently by providers and caregivers. Both groups generally believed that HIV-infected children would have typical ECD if adherent to their HIV treatment. Conclusions . Important considerations regarding ECD in this population were uncovered. Understanding provider and caregiver perspectives' on ECD in HIV-exposed children is critical for promoting ECD in this community.